A new algorithm to estimate Sea-Ice Thickness in the Ross Sea from SSM/I brightness temperatures - Giuseppe Aulicino; Giannetta Fusco; Giorgio Budillon (2009)
In the polar regions, interactions between atmosphere and ocean are strongly influenced by presence and thickness of the ice cover, which forms an insulating layer over the ocean, hindering sensible heat fluxes and forming an effective barrier to evaporation, thus preventing latent heat loss. Since satellite passive microwave observations became available in the 1970s, significant progress has been made in the study of snow depth and sea-ice concentration and extent in these regions. Estimating sea-ice thickness from satellite data, instead, turned out to be really more difficult. In this work, a new algorithm (Ice and Snow Thickness – IST-08) was implemented to estimate sea ice and snow thickness in the Ross Sea from SSM/I brightness temperatures, using two ice classification parameters, based on microwave polarization and spectral gradient information. Results were validated with in situ sea-ice thickness data coming from NIC-NCDC campaigns in the year 1994, and showed a very good correlation (~ 0.91).